2019
DOI: 10.1111/jvim.15548
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and tissue angiotensin‐converting enzyme 2 activity and plasma equilibrium concentrations of angiotensin peptides in dogs with heart disease

Abstract: Background Angiotensin‐converting enzyme 2 (ACE2) is a homologue of angiotensin‐converting enzyme (ACE) and produces angiotensin peptides (APs), such as angiotensin 1‐9 and 1‐7 that are vasodilatory and natriuretic, and act to counterbalance angiotensin II. Hypothesis Evidence of ACE2 can be found in tissues and plasma of dogs. Equilibrium concentrations of renin angiotensin aldosterone system (RAAS) APs differ in dogs with heart disease compared to healthy dogs and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 68 publications
2
40
0
Order By: Relevance
“…The major end‐metabolites of the classical RAAS are angiotensin II and aldosterone, both of which directly or indirectly mediate sodium and water retention, vasoconstriction, and pathological remodeling of cardiac, vascular, and renal tissues . Recent reports describe an alternative RAAS pathway mediated by ACE2, prolyl‐carboxy‐peptidase 16, prolyl‐endo‐peptidase, and neprilysin, with production of the metabolites angiotensin 1‐9, angiotensin 1‐7 and angiotensin 1‐5 in people and dogs . Additional metabolites within this cascade have also been discovered including angiotensin 2‐10, angiotensin 2‐7, and angiotensin 3‐7 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The major end‐metabolites of the classical RAAS are angiotensin II and aldosterone, both of which directly or indirectly mediate sodium and water retention, vasoconstriction, and pathological remodeling of cardiac, vascular, and renal tissues . Recent reports describe an alternative RAAS pathway mediated by ACE2, prolyl‐carboxy‐peptidase 16, prolyl‐endo‐peptidase, and neprilysin, with production of the metabolites angiotensin 1‐9, angiotensin 1‐7 and angiotensin 1‐5 in people and dogs . Additional metabolites within this cascade have also been discovered including angiotensin 2‐10, angiotensin 2‐7, and angiotensin 3‐7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the RAAS has historically been challenging to investigate, renin‐angiotensin system equilibrium analysis has emerged as a novel technique that allows for comprehensive evaluation of this complex neurohormonal system. Catalyzing enzymes other than ACE (such as ACE2, neprilysin, chymase, and aminopeptidases) mediate production of RAAS metabolites in this pathway, and recent publications have begun to shed light on blood and tissue activities in dogs . This methodology has shown that ACE‐inhibitors not only suppress angiotensin II formation, but also increase levels of the beneficial peptide hormone angiotensin 1‐7, which is known to be metabolized to angiotensin 1‐5 by the N‐domain of ACE .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations